A tighter constraint on Earth-system sensitivity from long-term temperature and carbon-cycle observations - Tony E. Wong (Nature Portfolio, 2021)
Earth-system sensitivity (ESS) describes the long-term temperature response for a given change in atmospheric CO2 and, as such, is a crucial parameter to assess future climate change. Here, the authors use a Bayesian model with data from the last 420 Myrs to reduce uncertainties and estimate ESS to be around 3.4 °C.